OPTIMAL TIMING FOR ORBITAL FLOOR FRACTURE SURGERY: A COMPREHENSIVE SYSTEMATIC REVIEW AND META-ANALYSIS OF CLINICAL AND AESTHETIC OUTCOMES - Ni Putu Gita Raditya Sanjiwani; Gede Wara Samsarga; Kavita Wadde; Joshua Meng Hee Ding; Erk Evren; Tarun Bhagchandani (Jurnal Rekonstruksi dan Estetik, 2026)
Highlights: Early surgical repair (<14 days) significantly reduces the risk of persistent postoperative diplopia compared to delayed intervention (RR 0.43; 95% CI 0.21–0.89; p = 0.02). Postoperative enophthalmos rates are markedly low following early repair (2%), indicating superior orbital volume restoration, although reported data remain heterogeneous. Despite overall functional benefit, residual ocular motility impairment persists in ~9% of early-treated patients, highlighting the need for refined surgical techniques and standardized outcome reporting. Abstract Introduction: The optimal timing of surgical intervention for orbital floor fractures remains a subject of ongoing clinical debate. Although early repair is thought to prevent long-term functional and aesthetic complications, evidence from previous studies has been inconsistent. This systematic review and meta-analysis aimed to evaluate the functional and aesthetic outcomes of early (<14 days) versus delayed (≥14 days) surgical repair, particularly regarding ocular motility dysfunction, enophthalmos, and diplopia. Methods: A comprehensive literature search of PubMed, Embase, Scopus, Cochrane Library, and Web of Science was conducted to identify comparative studies evaluating the timing of surgical intervention for orbital floor fractures. Results: A total of six studies met the inclusion criteria, comprising 2,769 patients. Early repair significantly reduced the risk of persistent diplopia (RR 0.43; 95% CI 0.21–0.89; p = 0.02), although substantial heterogeneity was observed (I² = 83%). Proportional meta-analysis of early repair demonstrated a low pooled incidence of postoperative enophthalmos (2%; 95% CI 0.00–0.06), despite high heterogeneity (I² = 98.5%). Residual ocular motility dysfunction persisted in 9% of patients (95% CI 0.05–0.13), with minimal heterogeneity (I² = 0%). Conclusion: Early surgical repair of orbital floor fractures is associated with significantly improved functional outcomes, particularly a lower incidence of persistent diplopia and favorable aesthetic outcomes with low rates of enophthalmos. Nevertheless, the incomplete restoration of ocular motility in some patients underscores the importance of meticulous surgical technique and appropriate patient selection. Future high-quality prospective studies with standardized diagnostic criteria, surgical timing, and outcome measures are warranted.